The composition of the essential oil of Artemisia annua L. growing wild in Iran - Hossein Lari yazdi; Ramezanali Khavarinejad; Abdolhossein Roustaian (Institue of Medicinal Plants, ACECR, 2002)
The composition of essential oil of the leaves of Artemisia annua L. growing wild in Iran, were determined by the use of GC/MS. The leaf essential oils obtained by hydrodistilation. Predominantly comprised monoterpenids and the main constituents were α-Pinene (7.8713.28%), 1,8-Cineole (5.77-17.26%), Artemisia ketone (1.44-6.97%), Camphor (14.2629.05%) and Pinocarvone (3.64-8.04%). The principal sesquiterpenes were β-Caryphyllen (3.43-9.37%), Germacrene-D (3.07-6.26%) and β-Selinene (0.46-10.36%).